2019
DOI: 10.1111/eje.12411
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of dental undergraduate students towards patient safety in a UK dental school

Abstract: Objectives: Patient safety is an important issue in health care. In the United Kingdom, wrong site tooth extraction contributes to a significant proportion of adverse or harmful events, coined "never events." Therefore, patient safety within the field of dentistry is of paramount importance. This novel study aims to explore the teaching of patient safety to undergraduate dental students and their current attitudes to the subject. Methods: Focus groups were held at Barts' and The London School of Medicine andDe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…This variable view by staff of student understanding of patient safety is at odds with a recent survey of UK dental students that found students had a positive attitude and sound understanding of patient safety. 9 In our survey, one third of the teaching staff stated that patient experience was improved due to increased staff supervision of undergraduates: this has been demonstrated to improve patient outcomes. 27 Increased supervision also resulted in the higher quality teaching that was noted as a positive change by a quarter of aca- With most schools having a supervision ratio of 1:4 and an average of 80 students per year, it is a significant challenge to balance patient safety with sufficient clinical experience, as has been highlighted previously.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This variable view by staff of student understanding of patient safety is at odds with a recent survey of UK dental students that found students had a positive attitude and sound understanding of patient safety. 9 In our survey, one third of the teaching staff stated that patient experience was improved due to increased staff supervision of undergraduates: this has been demonstrated to improve patient outcomes. 27 Increased supervision also resulted in the higher quality teaching that was noted as a positive change by a quarter of aca- With most schools having a supervision ratio of 1:4 and an average of 80 students per year, it is a significant challenge to balance patient safety with sufficient clinical experience, as has been highlighted previously.…”
Section: Discussionmentioning
confidence: 83%
“…given. 9 As already emphasised, dentistry is a unique undergraduate course where there is the potential for patient harm as students develop their skills. This survey, however, also highlights the reduced student experience and fewer possibilities for autonomous practice due to the increasing levels of staff supervision as a result of an increased patient safety focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teaching and training are significant pillars for developing a patient safety culture. This should start at the undergraduate level 44,45 and the intention is that instilling an awareness of patient safety culture will endure throughout a dental professional’s career. 18…”
Section: Potential For Over-regulationmentioning
confidence: 99%
“…Training is essential for dealing with the problems that professionals may face during their careers 58,59,60 , and it is important to incorporate the theme of patient safety starting in the early years of undergraduate school 61 . One study 39 of Dentistry students identified predisposing human factors related to AE such as operator fatigue, unawareness of risks, and failures of referrals.…”
Section: The Problem's Size and Understanding Its Causesmentioning
confidence: 99%